EFL SPEAKING STUDENTS’ ATTITUDES TOWARDS TASK-BASED LANGUAGE TEACHING - Alhomaidan, Dr. Abdullah M. A. (IJRDO- Journal of Educational Research, 2017)
This study explores the value of task-based language teaching in English as a foreign language(EFL) speaking classes from the perspective of forty intermediate level students studying in atechnical Saudi Arabian college, who had been extensively exposed to this type of teaching. Severalresearch hypotheses were formulated on the basis of a comprehensive literature review ofscholarship on speaking and task-based language teaching and then tested in this research context.The study uses quantitative data derived from anonymous, semi-structured questionnairesdistributed to students. The results of this study show that the majority of respondents appear tohold an overwhelmingly positive attitude regarding the employment of task-based languageteaching in their speaking courses.